Telomerase Inhibition by Everolimus Suppresses Smooth Muscle Cell Proliferation and Neointima Formation Through Epigenetic Gene Silencing - Jun Aono, MD, PhD; Ernesto Ruiz-Rodriguez, MD; Hua Qing, MD; Hannes M. Findeisen, MD; Karrie L. Jones, BS; Elizabeth B. Heywood, MS; Dennis Bruemmer, MD, PhD (JACC: Basic to Translational Science, 2016)
Proliferation of smooth muscle cells (SMCs) during neointima formation is prevented by drug-eluting stents. The replicative capacity of mammalian cells is enhanced by telomerase expression; however, the contribution of telomerase to the proliferative response underlying neointima formation and its potential role as a pharmacological target are unknown. The present study investigated the mechanisms underlying the mitogenic function of telomerase, and tested the hypothesis that everolimus, which is commonly used on drug-eluting stents, suppresses SMC proliferation by targeting telomerase. Inhibition of neointima formation by everolimus was lost in mice overexpressing telomerase reverse transcriptase (TERT), indicating that repression of telomerase confers the anti-proliferative efficacy of everolimus. Everolimus reduced TERT expression in SMC through an Ets-1-dependent inhibition of promoter activation. The inhibition of TERT-dependent SMC proliferation by everolimus occurred in the absence of telomere shortening but rather as a result of a G1→S-phase arrest. Although everolimus failed to inhibit phosphorylation of the retinoblastoma protein as the gatekeeper of S-phase entry, it potently repressed downstream target genes. Chromatin immunoprecipitation assays demonstrated that TERT induced E2F binding to S-phase gene promoters and supported histone acetylation. These effects were sensitive to inhibition by everolimus. These results characterize telomerase as a previously unrecognized target for the antiproliferative activity of everolimus, and further identify a novel mitogenic pathway in SMC that depends on the epigenetic activation of S-phase gene promoters by TERT.